A protocol of systematic review and meta-analysis of narrow band imaging endoscopy in detection of early gastric cancer. Issue 33 (14th August 2020) - Zhang, Li; Liu, Xiao-yu; Zhong, Gang; Xin, Zhi; Sun, Xiang-Yu; Wang, Zhen-Yu
Abstract: Background: Early gastric cancer is the fifth common malignancy and the third leading cause of cancer death throughout the world. However, it is not clear how endoscopic screening for early gastric cancer affects incidence or mortality. We performed a systematic review and meta-analysis to evaluate the relationship between endoscopic screening for the mortality and incidence of early gastric cancer. Materials and methods: This protocol established in this study has been reported following the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols. Web of Science, PubMed, EMBASE, and the Cochrane Library were searched for cohort and case-control studies in cases without early gastric cancer until March 31, 2020. We will use a combination of Medical Subject Heading and free-text terms with various synonyms to search based on the Eligibility criteria. Two investigators independently reviewed the included studies and extracted relevant data. The relative risk and 95% confidence intervals were used as effect estimate. I-square test, substantial heterogeneity, sensitivity analysis, and publication bias assessment will be performed accordingly. Stata 15.0 and Review Manger 5.3 are used for meta-analysis and systematic review. Results: The results will be published in a peer-reviewed journal. Conclusion: The results of this review will be widely disseminated through peer-reviewed publications and conference presentations. This evidence may also provide helpful evidence of whether endoscopic screening would reduce the mortality and incidence of early gastric cancer. PROSPERO registration number: CRD42020171053